Unique features - Sakimin, Siti Zaharah (University Putra Malaysia, 2012)
Fruit has its unique features because of variability on their skin and pulp colour, shape as well as smell and aroma. All these factors influence their nutritional quality thus beneficial for good diet and healthy consumption.